Singapore's Experience In Attracting Foreign Direct Investment - Khoshimov Jakhongir Ravshanbek ugli (Periodica Journal, 2025)
The article examines the experience of Singapore in attracting foreign direct investment to the economy. Also, the possibilities of use in the conditions of Uzbekistan were studied. A scientific proposal and practical recommendations for improving the system of attracting foreign investments to the economy have been formulated
Keywords: foreign investments; foreign direct investments; investment climate attractiveness